Green Economy in the Post-pandemic Period: A Framework for Organizational Stakeholder Analysis - Kavvadia, Helen (Business and Economic Research, 2022)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">In the current geo-economic landscape, the satisfaction of green economy goals and post-pandemic economic recovery dominate public discussion. Although climate change consequences are increasingly evidenced, economic actors devastated by the economic impact of the COVID-19 crisis are tempted to prioritize some “less green” activity, as demonstrated at the fall 2021 G20 summit and the United Nations COP26 summit in Rome and Glasgow, respectively. This tendency is reflected in the indecision of economic actors in setting future goals, partly as a result of diverging stakeholder forces applied to organizations. Although stakeholders’ views are often not publicly known, they shape organizational policies. To understand the stance of organizations on the dilemma of “climate versus recovery,” it is therefore important to decipher the stance of their stakeholders concerning the two alternative priorities. This article provides a framework for analyzing stakeholders’ positions on this predicament based on how public or private their goals, consultations, and deliberations are. The validity of the proposed framework is tested in a case study approach through the examination of stakeholder preferences shaping the European Investment Bank’s (EIB) decision-making. The European Union’s (EU) bank has been chosen as a case study because it announced its “pivot” to become the first public international climate bank in 2019, and formed an important part of the Union’s first response to the COVID-19 pandemic resilience and stimulus initiatives.